The Influence Of Ta'zir On The Level Of Discipline Of Students Of Madrasah Diniyah Takmiliyah (Mdt) Al-Badriyyah Al-Ishlah Islamic Boarding School Bandar Kidul Mojoroto Kediri City - Irkhamuddin Irkhamuddin; Nur Azizi; Mahmudi Mahmudi; Zaidus Surur Umamul Barik (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2024)
Ta'zir in Islamic education is an act that is carried out consciously by the educator by giving warnings and lessons to students for violations that have been committed in accordance with Islamic values ​​and principles in accordance with the weight of the violations they have committed. The more serious the violation, the more severe the punishment will be. The issues that can be raised in this research are: (1) how is the implementation of ta'zir in Madrasah Diniyah Takmiliyah Al-Badriyyah? (2) is there any influence of ta'zir on the level of discipline of Madrasah Diniyah Takmiliyah Al-Badriyyah students? While this study aims to determine the application of ta'zir and the effect of ta'zir on the discipline of Madrasah Diniyah Takmiliyah Al-Badriyyah students. The approach that the author uses is a quantitative approach. This study uses the method of observation, interviews, questionnaires and documentation. With a sample of 84 respondents. Data collection in this study used a questionnaire instrument to obtain variable (X) and variable (Y) data. Testing the validity and reliability shows that the ta'zir questionnaire instrument on student discipline at Madrasah Diniyah Takmiliyah Al-Badriyyah shows valid and reliable results. Based on the hypothesis test, it is known that ta'zir influences the discipline of Madrasah Diniyah Takmiliyah Al-Badriyyah students. This is evidenced by the results of a simple regression test analysis, the value of F count = 0.008. And it can be seen that the R Square value is 0.620, which means that there is a strong influence between the ta'zir variables simultaneously on the disciplinary variable by 62%. From these results it means that there is a significant influence between ta'zir on the discipline of Madrasah Diniyah Takmiliyah Al-Badriyyah students. This shows that the application of ta'zir following teaching and learning in relation to the discipline of Madrasah Diniyah Takmiliyah Al-Badriyyah students is well proven empirically.